POLA KOMUNIKASI ORANG TUA DALAM PEMBINAAN ANAK PUTUS SEKOLAH DI KENAGARIAN RANAH PALABI KECAMATAN TIMPEH KABUPATEN DHARMASRAYA - Panca Anggraini (JIP: Jurnal Ilmu Pendidikan, 2024)
This thesis is entitled "Communication Patterns of Parents in Coaching School Dropouts in Kenagarian Ranah Palabi Timpeh District Dharmasraya Regency". This research is motivated by most dropouts in the nagari ranah palabi sub-district timpeh dharmasraya district who tend to be rude in speaking, many of the dropouts like to say dirty words. In addition, in the nonverbal aspect, dropouts when communicating like not paying attention to the interlocutor even though the interlocutor is older and often cut off other people's conversations, while with their peers they often hit, slap and push their heads. From this fact, the author wants to find answers about parents' communication patterns in fostering school dropouts. This research is in the form of qualitative research and is descriptive. Data sources consist of primary data, namely, dropouts, parents of dropouts, head of the jorong and people who interact with dropouts. The data collection methods used are observation, interview and documentation. The results of the study are the Communication Patterns of Parents in Coaching Dropout Children in Kenagarian Ranah Palabi Timpeh District, Dharmasraya Regency, which consists of, first: communication patterns, where there are problems in the form of supporting and inhibiting factors for parents' communication patterns in coaching dropout children. Second: communication patterns, where there are problems of communication patterns.